EFFECT OF SOUIUM BICARBONATE ON HATCHING AND ON POSTEMBRYONIC GROWTH OF BRACHYDANIO RERIO, CYPRINUS CARPIO, LABEO ROHITA, CIRRHINUS MRIGALA AND CATLA CATLA.
The treatment of sodium ’bicarbonate at the dosage of 100 to 1000 mg /litre has been tested ex